"La Belle Liégeoise", the new footbridge in Liège. (13th September 2017) - Gens, Frédéric; Servais, Vincent
ABSTRACT: The new footbridge in Liège, known as "La Belle Liégeoise", was opened on 2 May 2016. Located upstream of the landscape window created by the new Guillemins Esplanade, this bridge provides a connection for soft transport modes from the railway station across the Meuse to La Boverie Park, maintaining clearance for navigation. The site presents a dissymmetry: an urban bank faces a wooded bank. Reflecting this, the structure of the main section on the left bank develops a suspended typology, while the second section on the right bank is supported by struts. The main span over the Meuse is 163 metres for a total length of 294 metres. The 5.5 metre wide decking is positioned laterally to the supporting structure. The footbridge is accessible to "soft" transport modes via the provision of ramps made of variable height steel boxes, supporting the 3.5 metre wide decking of azobé wood. On the right bank, the bridge crosses La Boverie Park through the canopy, offering a new vision of this urban park. The desire to design a thin and elegant structure integrated into the site, combined with the need to restrict navigation on the Meuse as little as possible, led to the obvious use of steel for the main structure. Construction involved 740 tonnes of steel. Structural elements 15 metres long were trucked onto a temporary assembly site. These elements were assembled on the ground in six sections, the largest weighing 400 tonnes for a 150 metre length. These six sections were finally transported by barge, lifted and positioned by three floating cranes. The most impressive section, consisting of the suspended part, was transported horizontally before being re‐erected on site. Finite element analysis was used to determine the reduction elements and check for strength and stability. Funicular geometry tends to maximize the axial forces of elements. For some critical elements (hangers, suspension, pylon, etc.) non‐linear calculations were performed. The same applied for determining the reverse deflection, which reaches 160 cm in the main span. Adopting a minimalist design for the nodes, the hanger connections are welded, meaning the screed or assembly members do not have to be visible. This particularly slender type of structure is sensitive with respect to its vibratory dynamic behaviour. Tuned mass dampers were designed to allow the project to meet the required conditions of comfort. Bureau Greisch, in association with the landscaping architect Corajoud, was responsible for the full architectural and structural design for the footbridge.